Feminist Movement in India – an overview (International Journal of Food and Nutritional Sciences, 2022)
Feminism as an ideologydeveloped in the West in the 18th century. The evolution of Western Feminist history can be understood in four stages, known as the various “waves” of feminism. Feminism developed in India during the 19th century. Feminism in present-day India has been showing some encouraging trends for various reasons. The paper analyses the history of feminism in the West as well as in India. It attempts to examine the changing trends in the feminist movement in India, in keeping with the changes that have taken place in Indian society and also at the global level. The paper focuses on some current issues which the contemporary feminists in India have taken up and the new strategies and methods used by them to resolve those issues. It also analyses one of the contemporary feminist movements as an example. Thus, the paper is an overview of the feminist movement in India.